Migration, Squatting and Radical Autonomy (2017)
This book offers a unique contribution, exploring how the intersections among migrants and radical squatter’s movements have evolved over past decades. The complexity and importance of squatting practices are analyzed from a bottom-up perspective, to demonstrate how the spaces of squatting can be transformed by migrants. With contributions from scholars, scholar-activists, and activists, this book provides unique insights into how squatting has offered an alternative to dominant anti-immigrant policies, and the implications of squatting on the social acceptance of migrants. It illustrates the different mechanisms of protest followed in solidarity by migrant squatters and Social Center activists, when discrimination comes from above or below, and explores how can different spatialities be conceived and realized by radical practices.